2015
DOI: 10.1007/s11102-015-0652-7
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary incidentalomas: analysis of a neuroradiological cohort

Abstract: In concordance with available literature, adenomas are the most frequent incidentally found pituitary lesions. Hormonal dysfunction is quite prevalent, including symptomatic presentations, which suggests that there seems to be a low sensitivity for the diagnosis of pituitary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 16 publications
2
19
1
Order By: Relevance
“…In this paper, our stricter inclusion criteria, our large cohort with a long follow-up allowed us to bet- ter define some of the characteristics of the most common type of PIs. CNPIs in our cohort were more commonly diagnosed during the fifth decade and in female patients, similarly to other studies [4,6,7]. While micro and macroadenomas were almost equally represented, we found a significant difference in tumor size between genders, with men more likely to have a macroadenoma.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In this paper, our stricter inclusion criteria, our large cohort with a long follow-up allowed us to bet- ter define some of the characteristics of the most common type of PIs. CNPIs in our cohort were more commonly diagnosed during the fifth decade and in female patients, similarly to other studies [4,6,7]. While micro and macroadenomas were almost equally represented, we found a significant difference in tumor size between genders, with men more likely to have a macroadenoma.…”
Section: Discussionsupporting
confidence: 89%
“…The association of headache and pituitary masses is controversial [13], and we therefore decided to include only those patients in whom headache was judged not to be associated with the presence of the adenoma. This probably accounts for the lower figures for headache as an indication for imaging in our cohort compared to the one reported in other studies (11.9% vs. around 30% in published papers) [2,7]. While this might have led us to exclude some patients in which headache was not caused by the sellar mass, this have allowed us to be more confident that we have included only patients with an incidental imaging finding, that is, true PIs.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Possible explanations of this trend may be that most PI were detected on MRI and CT scans of the brain rather than that of the sella which may have missed smaller lesions. There is also a possibility that the radiologists may have under-reported small lesions, since another recent study reported a slightly higher proportion (37.5%) of microadenomas (15).…”
Section: Discussionmentioning
confidence: 99%